Pengaruh Pengambilan Keputusan, Pengharggan Komitmen Organisaasi Dan Motivasi Kerja Terhadap Kinerja Pegawai - Kaligis, Jenny Nancy (Program Pascasarjana STIE Amkop Makassar, 2023)
This research aims to analyze the influence of decision making, acknowledgment, organizational commitment, and work motivation towards employee’s perfomance at Bolaang Mongondow Timur regency. This research administrated at Dinas pendidikan Bolaang Mongondow Timur regency with the sample size n = 81. Casual survey was the method used implementing path analysis. The research findings showed that : 1) positive direct influence of decision making towards employee’s performance, 2) ) positive direct influence of acknowledgment making towards employee’s performance, 3) positive direct influence of organizational commitment towards employee’s performance, 4) positive direct influence of work motivation towards employee’s performance, 5) decision making, 6) acknoledgment, 7) organizational commitment had positive direct influence towards work motivation, 8) positive direct influence of acknowledgment toward decision making, and 9) positive direct influence of acknowledgment towards organization commitment. These findings recommend that to improve the employee’s work performance quality, need to have firmness in decision making, acknowledgment, organization commitment, and work motivation. Keywords : decision making, acknowledgment, organizational commitment, work motivation, employee’s’ performance.